Investigation of glyphosate removal from aqueous solutions using Fenton-like system based on calcium peroxide - Li, Fan; Shean, Thomas Yaw Choong; Soltani, Soroush; Abdullah, Luqman Chuah; Md. Jamil, Siti Nurul Ain; Amerhaider Nuar, Nurul Nazihah (Multidisciplinary Digital Publishing Institute, 2022)
Glyphosate [N-(phosphonomethyl)-glycine], an organophosphate broad-spectrum herbicide, is a serious environmental contaminant that poses a significant threat to humans. It can be detected as a contaminant in water; thus, effective procedures for its removal are urgently required. The present study investigated the performance of glyphosate removal from aqueous solutions using a Fenton-like system. Calcium peroxide (CaO2) was used as a source of hydroxyl free radicals with Fe2+ as a catalyst to trigger the Fenton reaction. Fourier transform infrared spectroscopy (FTIR), x-ray diffraction (XRD), and potassium permanganate titration were carried out for characterization of calcium peroxide. The effect of operating parameters such as pH, the molar ratio of Ca2+:Fe2+, the initial dosage of calcium peroxide, and the initial glyphosate concentration on the removal efficiency was studied, respectively. The maximum total phosphorus (TP) and chemical oxygen demand (COD) removal were 94.50% and 68.60%, respectively, within 120 min under optimal conditions (pH = 3.0, initial glyphosate concentration = 50 ppm, initial CaO2 dosage = 0.5 g, molar ratio of Ca2+:Fe2+ = 6, room temperature). Experimental data were analyzed using zero-order, first-order, second-order, and Behnajady, Modirshahla, and Ghanbary (BMG) kinetics models. The degradation kinetics of glyphosate could be mostly fitted with the BMG kinetics model. This study demonstrated that calcium peroxide could be considered an effective oxidant for glyphosate wastewater treatment.